Thermal Conductivity of Anode Cover Materials in Hall Heroult Cells - Hasini Wijayaratne (Canadian Institute of Mining, Metallurgy and Petroleum, 2011)
Anode cover material, a mixture of crushed electrolyte and alumina, is a crucial part of an aluminium reduction cell because of its important role in maintaining overall heat balance. However, until recently little attention has been given to understanding or controlling its composition and quality. The thermal conductivity of anode cover material determines the extent of the heat loss from the top of the cell. This will change as a function of the granulometry and composition of the applied cover as well as over time as the cover material consolidates on top of the cell. The ability to measure or predict the thermal conductivity of fresh and ageing cover is an important tool for managing cell heat balance. Recent studies have shown that granulometry or more correctly, voidage is likely to be the predominant determinant of thermal conductivity of anode cover materials. We have developed equipment to measure the thermal conductivity of granular cover material and tested the relative importance of composition (ratio of alumina to crushed electrolyte) and granulometry/voidage on cover thermal conductivity. In general, our results confirm that granulometry is the dominating factor. Generally, high voidages contribute to lowering the thermal conductivity especially when particles are mostly fine. However the relationships between granulometry, voidage and thermal conductivity are complex due to the varying nature of heat transfer between particles. Aging of granular cover material occur during cell operation forming a consolidated crust due to exposure to heat and fumes over time. Structure and thermal behaviour of this consolidated crust is also important in understanding the overall properties of cover. This paper presents the outcomes of laboratory studies conducted in order to understand the thermochemical behaviour of anode cover material and in particular, the role of fines in anode covers mixtures.